Use of CCAFS research outputs to prepare project reviews on climate change for World Bank investment projects - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
CCAFS research outputs were used to prepare quality reviews on climate change for World Bank agricultural projects, at various stages in the pipeline. Specifically, WB task teams were advised on the use of several CCAFS outputs including reports, knowledge platforms etc (and as necessary), with the goal to be better informed, while preparing new agricultural investment projects, on the several dimensions of climate change for the area of investment, and towards maximizing the adaptation and mitigation co-benefits of their projects.